2014
DOI: 10.1109/access.2014.2313957
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Agent-Based Modeling of Hospital Environments

Abstract: Agent-based modeling has become a viable alternative and complement-to-traditional analysis methods for studying complex social environments. In this paper, we survey the role of agent-based modeling within hospital settings, where agent-based models investigate patient flow and other operational issues as well as the dynamics of infection spread within hospitals or hospital units. While there is a rich history of simulation and modeling of hospitals and hospital units, relatively little work exists, which app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Simeone et al 2012) or other forms of flow graphs (Friesen and McLeod 2014) to supply the logic behind the simulated patient flow. They are applied in late stages of planning, i.e.…”
Section: Related Workmentioning
confidence: 98%
“…Simeone et al 2012) or other forms of flow graphs (Friesen and McLeod 2014) to supply the logic behind the simulated patient flow. They are applied in late stages of planning, i.e.…”
Section: Related Workmentioning
confidence: 98%
“…A review of related works in the area of ABM in health sector can be found in [20]. The case of ED was implemented by agent-based simulations with respect to evacuation [21], optimization scheduling [22], disease propagation analysis [23].…”
Section: Related Workmentioning
confidence: 99%
“…Nevertheless, hybrid modeling has tremendous potential regarding operational aspects, as demonstrated by Hamza et al, who combined discrete-event and agent-based modeling to simulate the operational patient throughput [ 22 ]. On the same note, Friesen et al have identified agent-based modeling as a simulation modeling paradigm with ‘tremendous potential’ while also pointing out the necessity to combine with other paradigms to construct an accurate simulation model [ 24 ].…”
Section: Introductionmentioning
confidence: 99%